The FAIR Accessor and the authenticity of digital archival information - Pacheco, André Pereira (2022)
The constant increase in digital information’s volume, variety, and complexity poses many problems that make it difficult to preserve archival information while ensuring that it remains authentic, reliable, accessible, trustworthy, intelligible, and reusable for as long as possible. This study explores the concepts of a possible implementation of a FAIR Accessor, a technology developed to provide Findable, Accessible, Interoperable, and Reusable research data, as an infrastructure that can support and aid archival information description and ensure its authenticity. A qualitative literature review on a selection of representative works in the f ields of Information Science, Diplomatics, and the FAIR principles is followed by a discussion on how the key concepts of each f ield overlay and thus may complement each other mutually. It is concluded that the infrastructure of the FAIR Accessor can prove useful in enriching archival description and, ultimately, in assisting to ascertaining the authenticity of records.